2017
DOI: 10.1002/ejlt.201600466
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient extraction of EPA/DHA‐enriched oil from cobia liver using homogenization plus sonication

Abstract: Cobia, Rachycentron canadum, is a species of marine finfish with emerging global potential for offshore aquaculture. The fillet processing by‐product, cobia liver, can be considered an accessible source of EPA/DHA‐enriched oil. Oils are mainly extracted with hexane in the oil industry; however, extractability is greatly decreased in wet biomass as the hydrophilic surface hinders the penetration of hexane into the tissue matrix. In this study, the feasibility of agitated extraction (AE), ultrasonic extraction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Kuo et al [ 62 ] observed a different trend with the decrease in the a* value (redness) and increase in the b* value (yellowness) as a result of the removal of some pigments during the cobia liver oil refining process. In fact, the bleaching process could remove some pigments and their secondary products—like aldehydes, ketones, trace metals, and sulfurous compounds—to modify the final color of the refined oil [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kuo et al [ 62 ] observed a different trend with the decrease in the a* value (redness) and increase in the b* value (yellowness) as a result of the removal of some pigments during the cobia liver oil refining process. In fact, the bleaching process could remove some pigments and their secondary products—like aldehydes, ketones, trace metals, and sulfurous compounds—to modify the final color of the refined oil [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed that oil from by-products can be successfully extracted and refined to remove some undesirable compounds (moisture, pigments, free fatty acids, phospholipids, minerals, off-flavours, etc.) which affect oil stability, overall quality and consumers’ acceptability, without the loss of PUFAs which enables its further application [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Routray et al obtained 19.18 g/100 g oil from salmon by-products using enzymes during the extraction process, and omega-3 PUFAs constituted a significant part [ 8 ]. Kuo et al used homogenization plus sonication to extract EPA/DHA-enriched oil from cobia liver, with 5.2% EPA and 19.7% DHA [ 9 ]. Oliveira et al adopted enzymatic hydrolysis to extract oil from yellowfin tuna, which presented high levels of EPA (6.05 g/100 g) and DHA (27.15 g/100 g) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%